2008
DOI: 10.1136/gut.2008.157461
|View full text |Cite
|
Sign up to set email alerts
|

Miniprobe confocal laser microscopy for the detection of invisible neoplasia in patients with Barrett's oesophagus

Abstract: Miniprobe CLM showed a high negative predictive value for the diagnosis of endoscopically invisible neoplasia in Barrett's oesophagus; sensitivity, however, has still to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
139
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(150 citation statements)
references
References 21 publications
3
139
2
6
Order By: Relevance
“…In further trials, pCLE showed a high negative predictive value (NPV) of 99%, however at the price of a somewhat lower PPV of only 44% [30]. Similar results were obtained from a trial in three expert centers assessing 68 patients with Barrett's esophagus.…”
Section: Endomicroscopy In the Esophagussupporting
confidence: 71%
“…In further trials, pCLE showed a high negative predictive value (NPV) of 99%, however at the price of a somewhat lower PPV of only 44% [30]. Similar results were obtained from a trial in three expert centers assessing 68 patients with Barrett's esophagus.…”
Section: Endomicroscopy In the Esophagussupporting
confidence: 71%
“…[3][4][5][6][7] Endoscopists are exploiting neovascularization in Barrett's esophagus to detect neoplasia using novel imaging modalities, such as narrow band imaging and confocal laser endomicroscopy. [8][9][10][11][12] One of the features that endoscopists look for is the vascular pattern under narrow band imaging or confocal laser endomicroscopy. [8][9][10][11][12] Irregular or increased vascularity is a feature that endoscopists are looking for with these imaging modalities to identify significant superficial neoplasia, including both high-grade dysplasia and esophageal adenocarcinoma.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] One of the features that endoscopists look for is the vascular pattern under narrow band imaging or confocal laser endomicroscopy. [8][9][10][11][12] Irregular or increased vascularity is a feature that endoscopists are looking for with these imaging modalities to identify significant superficial neoplasia, including both high-grade dysplasia and esophageal adenocarcinoma.…”
mentioning
confidence: 99%
“…др. [10][11][12]. Вместе с тем следует отметить, что изображения конфо-кальной эндомикроскопии по диапазону глубины обе-спечивают визуализацию только поверхности слизистой оболочки и, в отличие от обычного гистологического мето-да, не дают представления о структуре более глубоких слоев.…”
Section: диагностические возможностиunclassified